A Demand-Side Analysis of Intellectual Capital in the Accommodation Industry: The Case of the Youth Market in Slovenia - Nemec Rudež Helena (Naše gospodarstvo/Our economy, 2021)
To date, research on intellectual capital (IC) in tourism has dealt with the supply-side view. This study continues the research into IC and develops a new perspective dealing with the demand side of IC in the accommodation industry, focusing on young consumers. On the theoretical ground, the study adapts the supply-side IC indicators to the demand-side perspective. A convenience sampling approach is used, and data was collected from 150 students representing the youth market. Exploratory factor analysis (EFA) is used to identify the dimensions of human, customer and structural capital of the accommodation industry for the youth market. Five dimensions of IC perceived by the youth market are identified: ‘Employee attitudes towards work’ and ‘Employee qualification’ constitute human capital; ‘Connectedness with guests’ and ‘Accommodation reputation and image’ represent customer capital, and ‘Structural knowledge’ reflects structural capital for youth in the accommodation industry.